STRATEGI COLLABORATIVE GOVERNANCE DALAM IMPLEMENTASI KEBIJAKAN DIVERSIFIKASI PANGAN GUNA MENGURANGI KERAWANAN PANGAN DI SULAWESI TENGAH - Srifridayanti; Fachrul Reza (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2025)
Every country must begin to design alternative solutions to achieve food security in order to ensure a sustainable quality of life for people around the world. The attainment of food security in Indonesia is not derived from a single system, but rather consists of various interrelated subsystems that interact and collaborate to reduce food vulnerability. This study aims to conduct an in-depth analysis of Collaborative Governance strategies in the implementation of food diversification policies to reduce the level of food insecurity in Central Sulawesi. The research employs a qualitative descriptive approach. Descriptive research is one of the methods used to understand or portray the reality of the phenomena being studied. It seeks to describe or explain current events as they occur in the field, in order to generate data in the form of written and spoken words. The findings indicate that the Provincial Government of Central Sulawesi has established synergy through effective communication and coordination in accordance with the principles of Collaborative Governance. The provincial government has undertaken cross-sector collaboration efforts by implementing direct interventions in food-insecure areas, one of which is through the Food Sector Innovation Program, namely the Integrated Food Terminal and Transportation Innovation, abbreviated as Tetra Pandu. There are 20 (twenty) institutions actively participating in the Tetra Pandu innovation program. However, several challenges remain in achieving food security in Central Sulawesi, particularly concerning the supply of local non-rice food commodities. Questions arise regarding whether the existing supply of non-rice foods is sufficient to meet market demand, especially for household consumption, in the event that rice ceases to be the primary staple food of choice among the people of Central Sulawesi.